2021
DOI: 10.3892/etm.2021.9728
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin attenuates silica‑induced lung injury by reducing oxidative damage and inflammatory response

Abstract: Oxidative stress and the inflammatory response are two important mechanisms of silica-induced lung injury. Hesperetin (HSP) is a natural flavonoid compound that is found in citrus fruits and has been indicated to exhibit strong antioxidant and anti-inflammatory properties. The current study evaluated the protective effect of HSP on lung injury in rats exposed to silica. The results indicated that the degree of alveolitis and pulmonary fibrosis in the HSP-treated group was significantly decreased compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 79 publications
2
7
0
Order By: Relevance
“…Plants are significant sources of natural antioxidants, and the antioxidant activity of phenolic compounds has been widely recognized. Hesperetin [ 26 ], adelmidrol [ 27 ], and curcumin [ 28 ] upregulated the expression of GSH, SOD, and CAT, reduce MDA and ROS production, and suppress bleomycin- and silica-induced oxidative damage in pulmonary fibrosis. Nrf2 is the master activator for most of the antioxidant enzymes, and its expression was lower in the fibroblasts and myofibroblasts of patients with IPF [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plants are significant sources of natural antioxidants, and the antioxidant activity of phenolic compounds has been widely recognized. Hesperetin [ 26 ], adelmidrol [ 27 ], and curcumin [ 28 ] upregulated the expression of GSH, SOD, and CAT, reduce MDA and ROS production, and suppress bleomycin- and silica-induced oxidative damage in pulmonary fibrosis. Nrf2 is the master activator for most of the antioxidant enzymes, and its expression was lower in the fibroblasts and myofibroblasts of patients with IPF [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this result, we concluded that hesperetin plays a role in ALI and could potentially be exploited to develop novel anti-inflammatory therapies for VILI. Moreover, similar findings were observed in other publications with either hesperetin pretreatment (44) or postinsult administration (45,46). Hence, the role of hesperetin treatment in lung injury is significant, even though optimal timing and dosage warrants further study.…”
Section: Discussionsupporting
confidence: 86%
“…Rupatadine [96] Piroxicam [115] Nicorandil [123,124] Hesperetin [125] MicroRNA [126][127][128][129][130][131][132] Mesenchymal cells [133][134][135][136] Extracellular vesicles [137,138] The blockade of IL-9, a cytokine which belongs to Th2 cytokines, might also be of benefit. In silica-challenged mice, treatment with an anti-IL-9-neutralizing antibody inhibited lung fibrosis, as assessed by lung hydroxyproline level, and suppressed the levels of cytokines and chemokines IL-1β, IL-6, IL-12, CCL2, CXCL1, and TNFα in BALF [97,98].…”
Section: Other Agentsmentioning
confidence: 99%
“…Dioscin can also promote autophagy in macrophages, as demonstrated in silica-injured mice, where it reduced mitochondria-dependent apoptosis and cytokine production in alveolar macrophages [105]. The natural flavonoid compound hesperetin (HSP) decreased the extent of alveolitis and pulmonary fibrosis; reduced levels of MDA; increased the activities of antioxidant enzymes and total antioxidant capacity; inhibited the synthesis and secretion of TGFβ1; reduced pro-inflammatory cytokines IL-1β, IL-4, and TNFα; and increased the levels of anti-inflammatory factors IFN-γ and IL-10 in rats exposed to silica [125]. Similar effects of hesperetin, probably mediated via inhibition of NF-κB, were also observed in a rat model of ventilator-induced acute lung injury [160].…”
Section: Other Agents Reducing Inflammation and Fibrosismentioning
confidence: 99%